Nutraceutical Potential of Bitter Melon (Momordica charantia) on Cancer Treatment: An Overview of In Vitro and Animal Studies - Georgia-Eirini Deligiannidou; Agathi Pritsa; Anastasios Nikolaou; Efthymios Poulios; Christos Kontogiorgis; Sousana K. Papadopoulou; Constantinos Giaginis (Current Issues in Molecular Biology)
Bitter melon (Momordica charantia) has been extensively investigated for its potential in cancer treatment. In this work, we provide an overview of in vitro and animal studies exploring its bioactive compounds, extracts, extracellular vesicles, fusion proteins, co-treatment with conventional pharmaceuticals, and utilization of nanoparticles, demonstrating promising cytotoxic and apoptotic effects across various cancer cell lines. A comprehensive search of online databases, e.g., PubMed, Scopus, and Web of Science, and Google Scholar was performed in the last decade, utilizing relevant keywords and applying several inclusion and exclusion criteria. The plant and its derivatives exhibit significant antiproliferative properties and modulate key signaling pathways. Additionally, animal studies have validated its antitumor potential, highlighting its ability to suppress tumor growth, modulate immune responses, and enhance chemotherapeutic efficacy in vivo. Although several compounds of the plant have been investigated, the insights regarding their mechanisms of action remain limited. Also, plant-derived extracellular vesicles show promise as natural carriers for targeted drug delivery, while fusion proteins improve cellular uptake and apoptosis induction. Finally, the integration of bitter melon components into nanomedicine underscores their potential for advanced therapeutic applications. Collectively, these findings reinforce the growing interest in utilizing bitter melon-derived compounds for cancer treatment and signal the need for further research to optimize their clinical translation.